2020
DOI: 10.3390/cosmetics7040080
|View full text |Cite
|
Sign up to set email alerts
|

Retinol Has a Skin Dehydrating Effect That Can Be Improved by a Mixture of Water-Soluble Polysaccharides

Abstract: It is common that retinoids used in skincare can cause skin dryness, irritation and redness which is a complaint for the use of these molecules in skincare formulations. Objective: to investigate the influence of a mixture of polysaccharides to improve retinol-based formulations in a 12-day inner volar forearm study. Methods: in total, 22 inner volar forearms were treated over a 12-day topical application of a Placebo formulation containing 0.5% retinol verses a formulation containing 0.5% retinol and 3.0% of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
(23 reference statements)
0
3
0
Order By: Relevance
“…However, as was recently reported, retinol can have a dehydrating effect on the skin which, over time, may lead to increased skin erythema and flaking. 11 Technologies that enhance the skin permeability of retinol may allow formulators who are employing retinol to lower the active levels of the molecule which can help to mitigate the skin dehydrating effects. Methods to help improve the overall efficacy and safety of retinoid use can include, for example, encapsulation or incorporation of the retinoids into unique emulsion structures such as micro- or nanoemulsions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, as was recently reported, retinol can have a dehydrating effect on the skin which, over time, may lead to increased skin erythema and flaking. 11 Technologies that enhance the skin permeability of retinol may allow formulators who are employing retinol to lower the active levels of the molecule which can help to mitigate the skin dehydrating effects. Methods to help improve the overall efficacy and safety of retinoid use can include, for example, encapsulation or incorporation of the retinoids into unique emulsion structures such as micro- or nanoemulsions.…”
Section: Discussionmentioning
confidence: 99%
“…However, the use of retinol has been demonstrated to have a powerful skin dehydrating effect which can lead to skin dryness and potentially to skin irritation. 11 Recent work has demonstrated that jojoba oil, formulated as microemulsions, has the potential to enhance the penetration of various drugs through the skin. 12 In addition, previous work demonstrated that retinoids formulated in a soft colloidal nanocarrier system composed of jojoba oil could enhance the benefits of the retinoid in psoriatic patients.…”
Section: Introductionmentioning
confidence: 99%
“…Nephelium lappaceum leaf extract is an active that has been developed to replicate some of the mechanistic pathways observable for retinol (elastin and collagen stimulation, CCN1 inhibition), without some of the common drawbacks associated with retinol (stability, irritation). Although retinol's irritation potential is more anecdotal, with little literature to conclusively state that it is irritating, it is known to be drying [19], which should be avoided in a range designed for sensitive skin. Nephelium lappaceum leaf extract plays in the same territory as other actives or compounds, for example Bakuchiol, which aim to show similar efficacy to retinol, but without its downsides [20].…”
Section: Rejuvenate the Skin By Strengthening Crucial Dermal Fibresmentioning
confidence: 99%